DETERMINAN SIKAP MAHASISWA TERHADAP PENDIDIKAN KEWIRAUSAHAAN - Kukuh Mulyanto (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2016)
Entrepreneurship education was introduced into the schoolscurriculum with the aim of providing knowledge directed towardsdeveloping the students skills, and competences that will equip them to beinnovative, and to identify, create, and successfully manage business. Thisstudy is on the attitude of students towards entrepreneurial education inSTIE Totalwin Semarang. Questionnaire were the instrument used andsensus sampling technique was adopted. It was found out that, majorityof the respondents believes entrepreneurial education is a good policy andit has come to stay. Most student from the university are not keen andcommitted to entrepreneurship education because they seeentrepreneurship as menial and risky, and their ambition is to seek forsenior white-color job with certainty of income.